An Atlas of Contemporary Egypt - Bayoumi, Hala; Bennafla, Karine (Hors collection, 2023)
While several atlases of Ancient Egypt exist, no atlas of contemporary Egypt has yet been published. Thus, this work fills a void and offers the general public an illustrated panorama of Egypt at the beginning of the 21st century. Through the contributions of some fifty researchers, it presents in an accessible form the key facts and challenges that concern present-day Egypt in the realms of politics, economics, demographics, the environment, society and culture, and geopolitics. To this end, the Atlas relies on a wide array of previously unpublished sources, most especially maps, which help to unlock and interpret the results of the official Egyptian census of 2017, providing an up-to-date view of the country and a better understanding of Egypt today.